Induction of chlamydospores in pleurotus pulmonarius (grey oyster mushroom) as inoculum and development of lyophilized spawn - Sharul Aida Mohd Shayuti (School of Bioprocess Engineering, 2017)
P. pulmonarius spawn were selected for this study. Cultivation medium which was used to culture P. pulmonarius was Potato Dextrose Agar medium (PDA). In this study, induced chlamydospore was evaluated as a substitute for tissue and spore as inoculum in the preparation of improved P. pulmonarius spawn. Lyophilization was applied as the preservation technique of the spawn to increase shelf life. D-glucose soluble starch medium was selected as stress medium among the six types of stress medium due to its highest production of chlamydospores.